2017
DOI: 10.1159/000485744
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy of the Upper Arm

Abstract: Objective: To present a case of a 6-month-old infant with melanotic neuroectodermal tumor of infancy (MNTI) in the upper arm. Clinical Presentation and Intervention: A 6-month-old female presented with a well-circumscribed lesion of the upper arm at the Children's Hospital Zagreb. A biopsy was performed and microscopy revealed 2 cell populations consisting of small neuroblastic cells and larger melanin-containing epithelial cells. An excisional biopsy performed 1 month later confirmed the initial diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…3,4 Rare, non-head and neck sites include epididymis, [5][6][7] testis, 8,9 ovaries, 10 and soft tissue and bones of the extremities. [11][12][13][14] The largest retrospective study 2 that reviewed 472 reported cases within the literature showed mainly maxillary involvement in 279 cases (62.2%), followed by the skull (70; 15%), mandible (35; 7%), male reproductive system (23; 5%), central nervous system (20; 4%), soft tissue (7; 1%), and female reproductive system (3; ,1%). They also determined that the median age of diagnosis was 5 months.…”
mentioning
confidence: 99%
“…3,4 Rare, non-head and neck sites include epididymis, [5][6][7] testis, 8,9 ovaries, 10 and soft tissue and bones of the extremities. [11][12][13][14] The largest retrospective study 2 that reviewed 472 reported cases within the literature showed mainly maxillary involvement in 279 cases (62.2%), followed by the skull (70; 15%), mandible (35; 7%), male reproductive system (23; 5%), central nervous system (20; 4%), soft tissue (7; 1%), and female reproductive system (3; ,1%). They also determined that the median age of diagnosis was 5 months.…”
mentioning
confidence: 99%
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…The tumor is localized most often in the head and neck region, with maxilla (62.2%), skull (15.6%) and mandible (7.8%) being the most common anatomical sites [1]. Localizations of MNTI within epididymis, extremities, ovary and endolymphatic sac have also been reported [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%